Smart nano-architectures for neuroscience and neuroengineering: from properties to applications - Nurul Akmal, Che Lah; Shmoel, Nava; Trigueros, Sonia (Frontiers Media SA, 2024)
Nanotechnology, with its innovations in nanoarchitecture, has emerged as a powerful tool for addressing major global challenges. From revolutionizing healthcare to bolstering food security, its potential is vast. Despite these advancements, numerous unresolved issues remain, particularly concerning their potential role in supporting cancer development and progression. The scientific pursuit is complex, with researchers investigating whether a unified theory could link continuum/molecular-level quantum mechanics with neural circuitry theory. Such a theory would provide a crucial framework for further safe and effective enhancements in performance.